Experimental investigation of the quasi-static and impact tests on the energy absorption characteristics of coupler rubber buffers used in railway vehicles. (October 2019) - Yao, Shuguang; Li, Zhixiang; Ma, Wen; Xu, Ping; Che, Quanwei
Coupler rubber buffers are widely used in high-speed trains, to dissipate the impact energy between vehicles. The rubber buffer consists of two groups of rubbers, which are pre-compressed and then installed into the frame body. This paper specifically focuses on the energy absorption characteristics of the rubber buffers. Firstly, quasi-static compression tests were carried out for one and three pairs of rubber sheets, and the relationship between the energy absorption responses, i.e. Eab n = n × Eab 1, Ediss n = n × Ediss 1, and Ea n = Ea 1, was obtained. Next, a series of quasi-static tests were performed for one pair of rubber sheet to investigate the energy absorption performance with different compression ratios of the rubber buffers. Then, impact tests with five impact velocities were conducted, and the coupler knuckle was destroyed when the impact velocity was 10.807 km/h. The results of the impact tests showed that with the increase of the impact velocity, the Eab, Ediss, and Ea of the rear buffer increased significantly, but the three responses of the front buffer did not increase much. Finally, the results of the impact tests and quasi-static tests were contrastively analyzed, which showed that with the increase of the stroke, the values of Eab, Ediss, and Ea increased. However, the increasing rates of the impact tests were higher than that of the quasi-static tests. The maximum value of Ea was 68.76% in the impact tests, which was relatively a high value for the vehicle coupler buffer. The energy capacity of the rear buffer for dynamic loading was determined as 22.98 kJ.